2003
DOI: 10.1038/sj.bjc.6600821
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-kinase expression profiles in human gastric cancer cell lines and their modulations with retinoic acids

Abstract: Many protein tyrosine kinases are key regulators involved in cellular growth, differentiation, development, apoptosis and signal transduction pathways. Obtaining a comprehensive tyrosine-kinase expression profile in tumour cells is essential to learning more about their oncogenic potentials and responses to various chemotherapeutic reagents -such as retinoic acid, which has been shown to suppress the growth of gastric cancer cells and modulate gene expression. Expression of tyrosine kinases in retionic acid-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…cDNA was prepared from human and mouse cell lines as described previously (17). Total RNA (10 g) from cell lines was used as the template for cDNA preparation in a 20-l reaction mixture.…”
Section: Methodsmentioning
confidence: 99%
“…cDNA was prepared from human and mouse cell lines as described previously (17). Total RNA (10 g) from cell lines was used as the template for cDNA preparation in a 20-l reaction mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Although many reports (Hirai et al, 1987;Maru et al, 1990;Robinson et al, 1996;Kao et al, 2003) have shown upregulation of EphA1 in CRCs, and more recently downregulation, mechanisms of downregulation have not been examined (Hafner et al, 2006). In seeking a mechanism for EphA1 downregulation, epigenetic silencing due to methylation analysis of a CpG island in the EphA1 gene was investigated.…”
Section: Epha1 Promoter Methylation Inversely Correlates With Epha1 Ementioning
confidence: 99%
“…In mice, EphA1 is expressed in many epithelial tissues including skin, kidney, liver and thymus (Coulthard et al, 2001). Over-expression of human EphA1 has been observed in prostate, gastric and colon carcinomas (Hirai et al, 1987;Maru et al, 1990;Robinson et al, 1996;Kao et al, 2003). More recently, significant downregulation of EphA1 was reported in non-melanoma skin cancers (Hafner et al, 2006).…”
mentioning
confidence: 99%
“…Genetic and epigenetic alterations play important roles in the development and progression of gastric cancer [1,2] . Considerable attention has been given to the potential role of tyrosine kinases in gastric cancer [3][4][5][6] . The Ephrin (Eph) receptors constitute the largest family of tyrosine kinase receptors [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%